Interplay between serine/threonine protein kinases and two-component systems in Mycobacterium tuberculosis environmental response - Sontag, Natalie (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2026-03.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Shumin Tan.; Committee: Ralph Isberg, Carol Kumamoto, and Andrew Camilli.; Keywords: Microbiology, Molecular biology, and Biochemistry